ORGANIZATION AND CONDUCT OF LABORATORY CLASSES IN THE MECHANICS SECTION USING MODERN INFORMATION TECHNOLOGY - Махмудова Нафосат Вали кизи (Web of Journals Publishing, 2025)
The paper deals with the problem of increasing the efficiency of training specialists in educational institutions. It is shown that the professional readiness of students as a personal quality and an essential prerequisite for the effective activity of a specialist, the successful performance of his duties, the correct use of knowledge and experience, helps to quickly adapt to working conditions, and contributes to further professional development.
Keywords: Laboratory classes, formation of educational and professional practical skills, form of training.